The Development of Performance Management Regulation of Civil Servants in Indonesia - Irsyad Ul Fikri (Universitas Medan Area, 2025)
The Industrial Revolution 4.0 and the development of information technology have reached the point where it is possible to create Artificial Intelligence (AI) that can replace most things humans can do. The government is affected by this change. Such rapid global developments demand improvements in the performance management of the State Civil Apparatus (ASN). ASN performance management is not only for assessing employee performance but also as a tool for improving employee performance. The shift in the perspective of ASN performance management is leading to a cascading approach, supporting agile work mechanisms in line with organizational needs and the implementation of continuous performance dialogues between leaders and employees. This research is qualitative and uses a descriptive method in trying to analyze the function of law in ASN performance management regulations since the enactment of Law No.5 of 2014 concerning the State Civil Apparatus until now. This study shows the importance of consistently and accountably implementing the principle of transparency as a general principle applicable in the management of civil servant performance in Indonesia.